The role of decision makers in the use of long-acting contraceptive methods in Indonesia - Diny Nahrudiani; Kemal N. Siregar (Jurnal EduHealth, 2024)
An effective contraceptive method for preventing pregnancy is the long-term contraceptive method (MKJP), but more women of childbearing age choose short-term contraceptive methods. The aim of this research is to analyze multiple logistic regression in analyzing the role of decision makers in the use of MKJP in Indonesia in 2017. This research uses secondary data which is the result of the 2017 SDKI with a total of 18661 respondents. The results of this study show that the variables that influence the use of MKJP are the decision maker (p = 0.000), age (p = 0.000), education (p = 0.000), place of residence (p = 0.001), visits by family planning field officers (p = 0.665), explanation family planning officers (p = 0.141). The conclusion of this research is that decision makers, age, education, and place of residence influence the use of MKJP in Indonesia. Meanwhile, visits by family planning officers and officers' explanations about contraception do not influence the use of MKJP in Indonesia.